Hox genes regulate asexual reproductive behavior and tissue segmentation in adult animals - Christopher P. Arnold (Nature Portfolio, 2021)
Hox genes are highly conserved and well-known for their role in segmental patterning during early development. Here, the authors identify an unreported role for Hox genes in the adult tissue patterning and fission behavior required for asexual reproduction in planarian flatworms.